The correlation between location and size of infarction toward the quality of life in acute ischemic stroke patients at Sanglah General Hospital, Bali, Indonesia - Mirani Ulfa Yusrika; Anak Agung Bagus Ngurah Nuartha; Ida Ayu Sri Wijayanti; Made Widhi Asih; Skolastika Savitri Sujatmiko (DiscoverSys Inc., 2020)
Background: Location and size of infarction in acute ischemic stroke can cause different levels of neurological deficits and disabilities according to the function of the area of brain whose blood flow is disrupted, thus affecting the quality of life in patients. This study was aimed to explore the correlation between location and size of infarction toward the quality of life in acute ischemic stroke patients in SanglahเGeneralเHospitalเDenpasar.Methods: A cross-sectional study was conducted among 41 acute ischemic stroke patients at NeurologyเCare Unit, SanglahเGeneral Hospital Denpasar duringเMay-September 2019. The location of the infarct was grouped by the cerebral area. The largest diameter of infarction determined the size of the infarct. Data were taken from head ComputedเTomography (CT) scan results to assess the location and size of infarction and Barthel Index (BI) to measure the quality of life-based on Activity of Daily Living (ADL). Data were analyzed using univariate and bivariate analysisเ(Chi-SquareเtestเwithเCramer’sเV for location and BI scores, Spearmanเtest for size and BI scores) on SPSSเversion 23 for Windows.Results: Most of the respondents were males 59.0%, the average age of 60.03±14.4 years, ischemic thrombus stroke (71.8%), subcortical infarction (41.0%), small size (≤ 1.5 cm) of infarction (48.7%), and independent criteria for Barthel Index Scores (23.1%). There were significant correlations between the location of infarction and BI scores (r=0.636; p<0.000) and the size of infarction and BI scores (r=0.553; p<0.000).Conclusion: Infarct that located in the cortical area with small size are related to independent or mild dependency outcome. Conversely, infarct that located and associated with a subcortical area with larger size are related to severe or total dependency.